The Influence of the COVID-19 Pandemic on Technology: Adoption in Health Care - Clipper, Bonnie (Nurse leader, 2020)
SARS-CoV-2 (coronavirus disease 2019 [COVID-19]) has affected nearly every aspect of our lives. It has certainly changed how we deliver health care. In part, it has accelerated the development and use of technology solutions in health care. These technology tools were originally identified as mechanisms that would make future care easier or better; however, these tech solutions amidst COVID-19 are now viewed as essential. The use of technology discussed in this article has been accelerated during the current crisis because technology can provide distance, safety for health care professionals and patients, faster results reporting, virtual visits, and more. As we move forward, technology will continue to be positioned to best address public health needs and improve care efficiencies, as well as develop treatments and vaccines. Specifically, this article explores the adoption and growth of technology tools including: telehealth, artificial intelligence, and robotics over the first 90 days of the COVID-19 pandemic in the United States.